The Effect Of Capital Structure Mediation On The Influence Of Liquidity And Profitability On Firm Value - Laprina Siahaan; Lambok DR Tampubolon; Deni Iskandar (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
The title of this research is "The Effect of Capital Structure Mediation on the Effect of Liquidity and Profitability on Firm Value". The purpose of this study is that real estate companies listed on the Indonesia Stock Exchange (IDX) know the factors that can affect Firm Value, as well as the effect of capital structure as a mediation. The independent variables used in this study are Liquidity, Profitability, and Capital Structure. The population used is the financial statements of real estate companies for the period 2016 to 2019. The purposive sampling method was used to take the research sample. There are at least 25 companies that were successfully taken in this study. The results of this study indicate that the Profitability and Capital Structure variables have a positive influence on Firm Value, while Liquidity does not. The coefficient of determination shows that 21% of the Firm value can be explained by using these three variables. Liquidity and Profitability have a negative influence on the Capital Structure. Also, the function of capital structure is able to mediate the effect of Liquidity on Firm Value, while Profitability does not. The coefficient of determination shows 38% of Firm Value which is associated with the variables of Liquidity, Profitability, and Capital Structure as mediation